2017
DOI: 10.1103/physrevc.95.044605
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of large α yields observed in Li6 -induced reactions

Abstract: Background: Large α yields have been reported over the years in reactions with 6 Li and 7 Li projectiles. Previous theoretical analyses have shown that the elastic breakup (EBU) mechanism (i.e., projectile breakup leaving the target in its ground state) is able to account only for a small fraction of the total α-inclusive breakup cross sections, pointing toward the dominance of nonelastic breakup (NEB) mechanisms. Purpose: We aim to provide a systematic study of the α-inclusive cross sections observed in nucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…The results presented in this work, along with those presented in previous works [7,8,13], indicate that the IAV model provides a reliable framework to calculate NEB cross sections. Possible applications to knockout reactions at intermediate energies are currently under study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The results presented in this work, along with those presented in previous works [7,8,13], indicate that the IAV model provides a reliable framework to calculate NEB cross sections. Possible applications to knockout reactions at intermediate energies are currently under study.…”
Section: Discussionsupporting
confidence: 76%
“…Recently , the model model has been re-examined by several groups [7][8][9][10][11][12]. Moreover a systematic study of the alpha productions in 6 Li induced reactions has been recently reported by Lei and Moro [13], in which the numerical calculations using the IAV model agree well with the experimental data.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…These works have concluded that the UT formula is incomplete, and must be supplemented with additional terms, as we show below. The comparison of the IAV and UT models with experimental data supports this interpretation [12][13][14][15][16][17] In general, the NEB will contain also contributions coming from the population of states below the breakup threshold of the x + A system (E x < 0). One would like to have a common framework to describe transfer to both continuum as well as bound states.…”
Section: Theoretical Frameworkmentioning
confidence: 76%
“…A detailed analysis of the 3,4 He angular distributions and energy spectra will be the subject of a forthcoming investigation, maybe in the framework of the model recently developed by Lei and Moro [36].…”
mentioning
confidence: 99%